Gambaran Peresepan Obat Antikolesterol Pada Pasien Geriatri di RS Bhayangkara Anton Soedjarwo Pontianak Periode Januari-Februari 2023 - Rayna Iza Azyra; Rika (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2024)
Hypercholesterolemia is a disease that is the main cause of total death in Indonesia and the world. The prevalence of hypercholesterolemia in the world is around 45%, in Southeast Asia around 30%, in Indonesia 35% and in West Kalimantan 37.7%. In handling it, the prescription picture is crucial to reduce the risk of errors inprescribing anticholesterol drugs. The purpose of this study was to determine how the prescription of anticholesterol drugs in geriatric patients at Bhayangkara Anton Soedjarwo Pontianak Hospital for the period January-February 2023. This study included quantitative descriptive research using medical record data of outpatient geriatric patients who received anticholesterol drugs. Determination of the amount of sample data with the Lemeshow formula obtained as many as 100 samples with simple random sampling technique. The results obtained were the most cholesterol sufferers at the age of 61-65 years as much as 22% with female gender as much as 56%. The most widely used anticholesterol drug is Atorvastatin as much as 78%, with a dose of 20 mg, the frequency of use once a day as much as 98%, and the most comorbidities are heart disease 49%. The results showed that the mostprescribed anti-cholesterolemia drug was Atorvastatin.